RIDDHI (HABENARIA INTERMEDIA D. WEAR): SIGNIFICANCE AND VERSATILITY IN VARIOUS ANCIENT AYURVEDIC NIGHNATU SCRIPTURES - Shalini; Ramakant Marde; Rajesh Kumar Mishra; Prabhat Kumar Srivastava; Divya Vij (AYUSHDHARA, 2020)
In Ayurveda treatment combines products derived from plants, animal, mineral, etc. Amongst all types of Ayurvedic preparations plant-based preparations play a significant and important role in the Ayurvedic healing process. Healing with medicinal plants is as old as mankind itself. We have been using medicinal plants since extremely long time. The use of plant based medicinal products and supplements have increased tremendously over the past three decades. Ṛddhi is an important member of Aṣṭavarga group of plants. Traditionally it is used in many herbal preparations for its rejuvenating and health promoting properties. Polyherbal formulation containing tubers of this herb possess properties viz. full of vital energy, high in antioxidants, and boosting immunity. The demand of this herb is increasing day by day but due to scarcity of this plant in wild, unaware about authentic botanical source, non-existing cultivation practices there is widespread problem of adulteration or substitution with other plants. So by taking into account the above situation this systematic review has conducted to find out authentic botanical source of Ṛddhi.